2000
DOI: 10.1161/01.atv.20.9.2100
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of 15-Lipoxygenase in Vascular Endothelium Accelerates Early Atherosclerosis in LDL Receptor–Deficient Mice

Abstract: Abstract-To study the possible role of the human lipid-oxidizing enzyme 15-lipoxygenase (15-LO) in atherosclerosis, we overexpressed it specifically in the vascular wall of C57B6/SJL mice by using the murine preproendothelin-1 promoter. The mice overexpressing 15-LO were crossbred with low density lipoprotein (LDL) receptor-deficient mice to investigate atherogenesis. High levels of 15-LO were expressed in the atherosclerotic lesion in the double-transgenic mice as assessed by immunohistochemistry. The double-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
131
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(139 citation statements)
references
References 46 publications
(52 reference statements)
7
131
0
1
Order By: Relevance
“…10 -12 A variety of vascular cells are able to express 12/15-LO, including endothelial cells, 13,14 smooth muscle cells, 13,14 and monocytes/macrophages. 13,15 Overexpression of 12/15-LO in mouse endothelial cells 16 and rabbit monocytes/macrophages 17 resulted in completely opposite effects: The former was proatherogenic and the latter antiatherogenic, which indicates a possibility that different cellular expression of 12/15-LO may have different effects on atherosclerosis or that species differences may exist.…”
mentioning
confidence: 99%
“…10 -12 A variety of vascular cells are able to express 12/15-LO, including endothelial cells, 13,14 smooth muscle cells, 13,14 and monocytes/macrophages. 13,15 Overexpression of 12/15-LO in mouse endothelial cells 16 and rabbit monocytes/macrophages 17 resulted in completely opposite effects: The former was proatherogenic and the latter antiatherogenic, which indicates a possibility that different cellular expression of 12/15-LO may have different effects on atherosclerosis or that species differences may exist.…”
mentioning
confidence: 99%
“…It is also known that 15-LOX1 and 12/15-LOX are involved in the oxidation of low density lipoprotein, a contributing factor in the pathogenesis of atherosclerosis (15, 16). Furthermore, using either transgenic or knock-out mice models, a number of studies have demonstrated that 15-LOX1 and its murine ortholog 12/15-LOX play a role in atherosclerosis and restenosis (17)(18)(19). In addition, human atheroma homogenates upon incubation with AA converted it mainly to .…”
Section: Vsmcmentioning
confidence: 99%
“…2,3 There are three major human LOs (hLOs), 5-, 12-, and 15-hLO, whose main difference is the position of dioxygen incorporation into arachidonic acid (AA) (C-5, C-12, or C-15). 4,5 These three hLO isozymes are of great interest to scientists because they have been shown to be involved in a variety of diseases; 5-hLO in prostate cancer 6,7 and asthma 8 , 12-hLO in immune disorders 9 and breast cancer 7,10,11 , and 15-hLO-1 in atherosclerosis 12 and colorectal cancer. 7,13 Due to their involvement in such diseases, a better understanding of the mode of inhibition of small molecules is necessary to aid in future rational drug design against specific LO isozymes.…”
Section: Introductionmentioning
confidence: 99%